Pengembangan desain dan peningkatan produksi kain tenun sutera motif Pucu’ Rebbung - Srikandi Srikandi; Erma Erma; Faizal Faizal (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner problems were (1) the production of sarong fabric and silk shirt pattern of pucu’ rebbung is still lacking, (2) knowledge of the development of the pucu’rebbung design for both sarong and silk shirt cloth is lacking, (3) design development skills pucu’ rebbung for sarong and silk shirt cloth is very lacking. The solutions offered to solve partner problems included (1) to increase the production of sarong fabric and motif silk or pucu’ rebbung fabric, (2) to increase the partner knowledge to develop a motif or pattern ofpucu’ rebbung, for sarong and silk shirt fabric, (3) to improve partner skills to develop designs of motifs or patterns of pucu’rebbung, for sarong and silk shirt fabrics, (4) to accompany the partner in order to apply pucu’ rebbung style designs for sarong and silk shirt fabric. The methods used were lecture, demonstration, discussion, question and answer, and involved with the partner to increase the production of the development of designs of motifs or patterns of pucu’ rebbung. The results achieved were as follows: (1) the production of sarong fabric and silk shirt fabric with pucu’ rebbung motif is availablequite a lot in the partner’s showroom, (2) the partner has knowledge of the development of pucu’ rebbung designs for both sarong and silk shirt fabrics, (3) the partner has the ability to develop pucu’ rebbung designs for sarong and silk shirt fabric.